Морально-психологічний та психоемоційний стан організації як показник якості менеджменту - Сушик, І. В.; Сушик, О. Г.; Sushyk, I. V.; Sushyk, A. G. (Видавництво Львівської політехніки, 2021)
Досліджено важливість формування та підтримки морально-психологічного та психоемоційного стану організації в системі управління. Доведено взаємозалежність якості менеджменту від дії соціально-психологічних методів управління, які впливають на свідомість працівників, на філософію відносин у компанії, їхні соціальні, етичні, ментальні та інші інтереси. Визначено складові здорового клімату в організації, способи їх формування та діагностики. Проаналізовано традиційні та інноваційні методи управління організацією. Окрему увагу звернено на такі інструменти і технології управління, як корпоративна культура, командоутворення, емоційний інтелект, корпоративний гумор тощо. Наведено зарубіжний досвід управлінських нововведень. Акцентовано на потребі відновлення психоемоційного здоров’я працівників організації в часи коронaвірусної інфекції COVID-19 та постковідні часи. Зроблено висновок про те, що морально-психологічний та психоемоційний стан організації є показником якісного менеджменту.

In today’s world, the process of developing and updating the concept of personnel management continues. Management methods, tools and technologies are being improved, innovative management technologies are being approved. Increasingly, the staff of the organization is seen as a base for the formation of its competitive advantages. Of particular importance is the environment in which the employee is. Moral and psychological atmosphere, psychological and emotional climate in the organization, formed and maintained corporate culture of the organization are components of the success of the organization, its competitive advantages, and, at the same time, an indicator of effective management. The relevance of the study is that in times of rapid technology development, in the pursuit of innovation, constant reorganization of the organization, the desire to make the employee more efficient and productive, the line of understanding between proactivity and employee productivity is lost. All this has a negative impact on productivity, physical and mental health, especially in difficult post-covid times. The main purpose of the proposed study is to analyze the importance of moral, psychological and psycho-emotional state of the organization as components of management. To achieve this goal, the following tasks are set: to give examples of traditional and innovative methods of personnel management, to prove the need to update the modern concept of management; show the components of a favorable moral, psychological and psycho-emotional climate of the organization, ways of their formation and diagnosis; to reveal the content and significance of corporate culture as a tool for managing the organization; show the effectiveness of innovative socio-psychological methods and technologies in the management of organizational behavior as team building, emotional intelligence, corporate humor, etc .; on the example of domestic and foreign experience to prove the need to restore the psycho-emotional health of employees in modern covid and post-covid times. Modern socio-psychological methods of management are generalized, the expediency of their application in the management of the organization is substantiated. A list of traditional and innovative methods of influencing staff, including foreign experience of management innovations. The components of a favorable moral-psychological and psycho-emotional climate of the organization, methods of their formation and diagnosis are determined. Special attention is paid to such innovative personal technologies as corporate culture, team building, emotional intelligence, corporate humor. The need to restore the psycho-emotional health of employees of the organization in modern covid times of fasting has been demonstrated by the example of foreign experience. It is concluded that the focus of management should be on the corporate well-being and psychological health of employees, psycho-emotional recovery and support in difficult times of the pandemic. The topic of finding solutions to the problem of psychological fatigue and excessive stress of employees, the search for new tools and technologies to restore psycho-emotional health in the postpandemic period.
Moral and psychological state of the company as an example of effective management
Keywords: психологічний клімат; корпоративна культура; командотворення; емоційна грамотність; корпоративний гумор; психоемоційне відновлення; постпандемічний період; psychological climate; corporate culture; team building; emotional literacy; corporate humor; psycho-emotional recovery; post-pandemic period; 316; 005